Effects of solvent formulations in electrolytes on fast charging of Li-ion cells. (1st September 2020) - Wu, Xianyang; Liu, Tianyi; Bai, Yaocai; Feng, Xu; Rahman, Muhammad Mominur; Sun, Cheng-Jun; Lin, Feng; Zhao, Kejie; Du, Zhijia
Abstract: Improving the fast charging performance of lithium ion batteries (LIBs) has the promise to increase the widespread adoption of electric vehicles (EVs). Electrolyte development plays an important role in enabling fast charging. In this study, fast charging performance of LIBs is studied with different electrolytes of 1.2 M LiPF6 in Ethylene Carbonate (EC)/Ethyl Methyl Carbonate (EMC)/co-solvents at 30/50/20 wt%. The co-solvents are methyl acetate (MA), ethyl acetate (EA), ethyl formate (EF), dimethyl carbonate (DMC) and EMC. Long term cycling performance under fast charging shows different capacity retention behaviors for different co-solvents. The structural changes in the electrode material are studied by X-ray absorption spectroscopy (XAS) and X-ray diffraction (XRD). The molarity changes in electrolyte is investigated by inductively coupled plasma-optical emission spectroscopy (ICP-OES). The electrode/electrolyte interfaces before and after fast charging are analyzed by X-ray photoemission spectroscopy (XPS). The characterization results are in good agreement with the long-term cycling performance. DMC shows the highest fast-charging capability among the five studied co-solvents due to its increased conductivity, improved electrode/electrolyte interface and stable electrode structural integrity.